Relative examination of antioxidative enzymatic activities in plantlets of Cardiospermum halicacabum L. differentiated from hypocotyls in in vivo and ex vitro environment - Anushi A. Jahan (Biotechnology Reports, 2014)
A plant regeneration protocol was devised for Cardiospermum halicacabum by means of aseptically extracted 7 days old hypocotyls forming adventitious shoots on Murashige and Skoog (MS) medium harmonized with 0.7 μM thidiazuron (TDZ) producing a maximum of 18.20 ± 0.98 number of shoots in 94% cultures following 4 weeks. Subsequent subculturing for five passages, on a medium without plant growth regulators, tempted the highest shoot number (40.00 ± 1.15) with an average shoot length of 6.53 ± 0.49 cm after the fourth subculture. Histological sections confirmed the formation of multiple buds from hypocotyl explants. The expression of antioxidant enzymes like superoxide dismutase, catalase, ascorbate peroxidase and glutathione reductase was found to be higher in acclimatized plants than in the in vitro cultured ones suggesting the involvement of these enzymes in shoot differentiation and in growth under external environment partly due to their ability to cope up with oxidative stress.